AFLP marker diversity in water yam (Dioscorea alata L.) - Egesi, Chiedozie N.; Asiedu, Robert; Ude, G.; Ogunyemi, S.; Egunjobi, J.K. (Cambridge University Press, 2006)
Amplified fragment length polymorphism (AFLP) markers were employed to assess intraspecific variability in water yam (Dioscorea alata L.). Fifty-three accessions of diverse geographic origins in West and Central Africa (Benin, Côte d'Ivoire, Ghana, Nigeria and Chad) and Puerto Rico were analysed using three AFLP primer combinations. Of the 342 amplification products generated, a mean of 53.4% were polymorphic. Genetic similarity coefficients ranged from 0.29 to 0.95. The accessions could be clustered into three major genetic groups with one outlier. Each group was a mixture of accessions of different geographical origin indicating that geography has not played a major role in the differentiation of the species. A few accessions clustered very tightly suggesting that there may be duplicate accessions in the collection. The wide genetic variation observed constitutes a good basis for genetic improvement of yam.